Vivências e ritualidades entre os jovens na festa da padroeira Sant’Ana em Anápolis, Goiás (2017-2021) - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This dissertation aims to investigate the role played by young people during the religious festivity dedicated to Sant'Ana in the municipality of Anápolis, Goiás. It is worth noting that this festivity covers the religious and social aspect. For this purpose, the party corresponding to the years 2017 to 2021 was used as the object of analysis. For this perspective we sought to find out in which moments young people contribute the most with the celebration. Among these we list the historical context of this festivity with the importance of the Franciscan friars in the constitution of this feast. In relation to this festivity its main objective is to identify in the typically religious rituals the participation of young people. In the early years of the feast of Sant'Ana popular Catholicism prevailed, as these celebrations took place in the house of the faithful residents, when building the chapel in 1871 this feast happened to take place in the religious temple with the presence of the priest. In relation to this festivity its main objective is to identify in the typically religious rituals the participation of young people. Over the years, it has become grand, encompassing many participants. Thus today it is possible to notice that the participation of young people happens in a more predominant way in social moments, in which they dedicate themselves to the assembly of the structure and the stalls of the party. In the years between 2020 and 2021 this festivity occurred in an atypical way. Due to the Coronavirus pandemic, the social part was not performed. Usually the feast in devotion to Sant'Ana usually takes place between the days 17 to 26 July. The methodological procedures were based on field research with participation in the festival and bibliographic, which included the reading of authors who who address the issue.
Experiences and rituals among young people at the feast of the patron Saint Sant’Ana in Anpapolis, Goiás (2017-2021)
Keywords: Festividade; Festa religiosa - Sant’Ana; Jovens - Festa de Sant'Ana; Ritualidades sagradas e profanas; Festivity; Festivity - Sant'Ana; Young people - Festivity - Sant'Ana; Sacred and profane rituals; CIENCIAS HUMANAS::HISTORIA; CIENCIAS HUMANAS::TEOLOGIA